Chemical Composition, Antioxidant, Anticancer, and Antibacterial Activities of Roots and Seeds of Ammi visnaga L. Methanol Extract - Ibrahim M. Aziz; Rawan M. Alshalan; Humaira Rizwana; Fetoon Alkhelaiwi; Abdulaziz M. Almuqrin; Reem M. Aljowaie; Noorah A. Alkubaisi (MDPI AG, 2024)
For centuries, plants and their components have been harnessed for therapeutic purposes, with Ammi visnaga L. (Khella) being no exception to this rich tradition. While existing studies have shed light on the cytotoxic and antimicrobial properties of seed extracts, there remains a noticeable gap in research about the antimicrobial, antioxidant, and anticancer potential of root extracts. This study seeks to address this gap by systematically examining methanol extracts derived from the roots of A. visnaga L. and comparing their effects with those of seed extracts specifically against breast cancer cells. Notably, absent from previous investigations, this study focuses on the comparative analysis of the antimicrobial, antioxidant, and anticancer activities of both root and seed extracts. The methanol extract obtained from A. visnaga L. seeds demonstrated a notably higher level of total phenolic content (TPC) than its root counterpart, measuring 366.57 ± 2.86 and 270.78 ± 2.86 mg GAE/g dry weight of the dry extract, respectively. In the evaluation of antioxidant activities using the DPPH method, the IC50 values for root and seed extracts were determined to be 193.46 ± 17.13 μg/mL and 227.19 ± 1.48 μg/mL, respectively. Turning our attention to cytotoxicity against breast cancer cells (MCF-7 and MDA-MB-231), both root and seed extracts displayed similar cytotoxic activities, with IC50 values of 92.45 ± 2.14 μg/mL and 75.43 ± 2.32 μg/mL, respectively. Furthermore, both root and seed extracts exhibited a noteworthy modulation of gene expression, upregulating the expression of caspase and Bax mRNA levels while concurrently suppressing the expression of anti-apoptotic genes (Bcl-xL and Bcl-2), thereby reinforcing their potential as anticancer agents. A. visnaga L. seed extract outperforms the root extract in antimicrobial activities, exhibiting lower minimum inhibitory concentrations (MICs) of 3.81 ± 0.24 to 125 ± 7.63 μg/mL. This highlights the seeds' potential as potent antibacterial agents, expanding their role in disease prevention. Overall, this study underscores the diverse therapeutic potentials of A. visnaga L. roots and seeds, contributing to the understanding of plant-derived extracts in mitigating disease risks.